DETERMINANTS OF TIME TO PULMONARY TUBERCULOSIS DEVELOPMENT IN TYPE II DIABETES MELLITUS PATIENTS AT A COMMUNITY HOSPITAL - Nichanan Nakwihok; Sunisa Ruangmuan; Sutee Nuket; Somkiattiyos Woradet; Bhunyabhadh Chaimay; Kawintida Jeenmuang (The Indonesian Journal of Public Health, 2026)
Introduction: Globally, tuberculosis (TB) continues to be a major public health challenge, especially among diabetic patients, who are 15% more likely to develop TB compared to the general population. Aims: This study aimed to determine the median time from the onset of type 2 diabetes mellitus (T2DM) to the diagnosis of pulmonary tuberculosis (PTB) among T2DM patients and to identify factors associated with this duration. Methods: This retrospective cohort study was conducted at the community hospital, Nakhon Sri Thammarat Province from 2019 to 2023. The study included 105 T2DM patients, including 35 patients with PTB and 70 patients without PTB during the follow-up period. The ratio among subjects was 1:2. Data were retrieved and extracted from electronic medical records. The outcome was time from T2DM onset to PTB diagnosis. Kaplan-Meier method was used to estimate the median time. Cox’s model was used to identify risk factors associated with PTB, presented as hazard ratios (HR) and 95 percent confidence interval (95%CI). Results: The median time was 8.06 years (95%CI: 1.50-8.68). The factors associated with PTB diagnosis were male sex (AHR = 2.14, 95%CI: 1.06-4.32), smoking (AHR = 3.62, 95%CI: 1.50-8.68), household contact with TB patients (AHR = 12.04, 95%CI: 2.25-64.22), and residence in crowded communities (AHR = 3.91, 95%CI: 1.55-9.84), after accounted for alcohol drinking. Conclusion: The strengthened surveillance and targeted health intervention should be launched and addressed the factors including smoking, household contact with TB patients, and residing in the crowded communities in order to reducing PTB among T2DM patients.